EFFECT OF CANOPY CLOSURE ON CHLOROPHYLL CONTENT AND ANATOMY STRUCTURE OF CASTANOPSIS BOISII LEAVES IN THE REGENERATION STAGE IN BAC GIANG AND HAI DUONG, VIET NAM - Thi Duong, Kieu; Van Quynh, Vuong; Thi Tho, Nguyen; Viet Hung, Nguyen (Journal of Forestry Science and Technology, 2017)
The research was conducted in Bac Giang and Hai Duong in order to determine the relationship between canopy closure and chlorophyll a, b content and some anatomical features of Castanopsis boisii leaves in the regeneration stage. The survey result of 41 leaves samples on 20 transects shows that chlorophyll a content of the regeneration Castanopsis boisii leaves ranges from 1.12 to 1.75 (mg/g), chlorophyll b is from 0.47 to 1.0 (mg/g). The ratio of chlorophyll a/b is allocated according to the different canopy levels from 1.75 -2.4. Chlorophyll a content in all canopy levels is much higher than chlorophyll b content. Chlorophyll a accounts for 64-70% of total chlorophyll content in the research leaf samples while chlorophyll b only counts for 30-36% of total chlorophyll content. The first step is to assess the regenerated Castanopsis boisii trees in area with common height of less than 2.5 meters and belonging to shade tolerant stage. Quadratic equation and logarithmic equation are used to reflect the relationship between canopy closure and some anatomical features with a coefficient of determination (R2) ranging from 0.31 to 0.59 indicating that the relationship is at the moderate level to the strong level. Through the regression equations, the study has identified that the light corresponding to canopy closure of 60% makes a difference on chlorophyll content and anatomical features of the regenerated Castanopsis boisii in the study area.